Cost-Effectiveness of Lorlatinib as a First-Line Therapy for Untreated Advanced Anaplastic Lymphoma Kinase-Positive Non-Small Cell Lung Cancer - Li, SiNi; Li, JianHe; Peng, LiuBao; Li, YaMin; Wan, XiaoMin (Frontiers in Oncology, 2021)
Introduction Recently, a phase III CROWN trial compared the efficacy of two anaplastic lymphoma kinase (ALK) inhibitors and demonstrated that lorlatinib displayed clinical improvement over crizotinib for advanced non-small cell lung cancer (NSCLC) patients. Therefore, the aim of this study was to estimate the cost-effectiveness of lorlatinib as a first-line therapy for patients with advanced ALK-positive (+) NSCLC. Materials and Methods A cost-effectiveness analysis was performed using a microsimulation model from the US payer perspective and a lifetime horizon (30 years) in patients with previous untreated advanced ALK+ NSCLC. Based on the CROWN trial, patient characteristics were obtained, and the transition probabilities were estimated. All direct costs were derived from official sources and published literature. The main outcomes of the model were total costs, incremental cost-effectiveness ratio (ICER), quality-adjusted life years (QALYs), and life years (LYs). One-way and probabilistic sensitivity analyses and multiple scenario analyses were conducted to test the robustness of the model outcomes. Results In the base case analysis, in which 1 million patients were simulated, treatment with lorlatinib or crizotinib as the first-line treatment was related to a mean cost of $909,758 and $616,230 (incremental cost: $293,528) and a mean survival of 4.81 QALYs and 4.09 QALYs (incremental QALY: 0.72) per patient, respectively. The main drivers of cost effectiveness were drug price and subsequent cost. PAS indicated that lorlatinib has 90% cost-effectiveness when compared to crizotinib when the willingness-to-pay (WTP) threshold in increased to $448,000/QALY. Scenario analysis demonstrated that lorlatinib has 100% cost-effectiveness at a WTP threshold of 200,000/QALY compared to crizotinib treatment when the price of lorlatinib is decreased to 75% ($424.5) of its original price. Conclusions In this study, lorlatinib was unlikely to be cost effective compared with crizotinib for patients with previously untreated advanced ALK+ NSCLC at a WTP threshold of 200,000/QALY.